Histological and Immunohistochemical Analysis of the Effects of Topical Melatonin Treatment Associated with Collagen Sponge and rhBMP-2 Protein on Bone Remodeling - Leticia Ferreira Montarele; Dimitrius Leonardo Pitol; Bruno Fiorelini Pereira; Sara Feldman; Valéria Paula Sassoli Fazan; João Paulo Mardegan Issa (Biomolecules, 2022)
Extensive bone defect healing is an important health issue not yet completely resolved. Different alternative treatments have been proposed but, in face of a critical bone defect, it is still very difficult to reach a complete regeneration, with the new-formed bone presenting all morphological and physiological characteristics of a normal, preinjury bone. Topical melatonin use has shown as a promising adjuvant for bone regeneration due to its positive effects on bone metabolism. Thus, to search for new, safe, biological techniques that promote bone repair and favor defect healing, we hypothesized that there is a synergistic effect of melatonin treatment associated with rhBMP-2 to guide bone regeneration. This study aimed to investigate bone repair effects of topical melatonin administration in different concentrations (1, 10, and 100 µg), associated or not with rhBMP-2. Surgical-induced bone defect healing was qualitatively evaluated through histopathological analysis by light microscopy. Additionally, quantitative stereology was performed in immunohistochemistry-prepared tissue to identify angiogenic, osteogenic, and osteoclastogenic factors. Quantification data were compared between groups by the ANOVA/Tukey test and differences were considered significant when p < 0.05. Our results showed that the presence of the scaffold in the bone defect hindered the process of bone repair because in the group treated with “blood clot + scaffold” the results of bone formation and immunolabeling were reduced in comparison with all other groups (treated with melatonin alone or in association with rhBMP-2). Statistical analysis revealed a significant difference between the control group (bone defect + blood clot), and groups treated with different concentrations of melatonin in association with rhBMP-2, indicating a positive effect of the association for bone repair. This treatment is promising once it becomes a new safe alternative technique for the clinical treatment of fractures, bone defects, and bone grafts. Our results support the hypothesis of the safe use of the association of melatonin and rhBMP-2 and have established a safe and effective dose for this experimental treatment.